INNOVATION IN DIGITAL MOTOR VEHICLE TAX PAYMENT THROUGH E-SAMSAT IN SIDOARJO REGENCY: CHALLENGES AND OPPORTUNITIES IN IMPLEMENTATION - Fa’izah, Meifa Nur; Mursyidah , Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the E-Samsat system for motor vehicle tax payments in Sidoarjo Regency, with a focus on its challenges and opportunities in enhancing efficiency and public compliance. Method: A mixed-methods approach was employed, combining qualitative and quantitative data through taxpayer surveys, interviews with government officials, and secondary sources such as governmental reports and prior studies on digital taxation. Qualitative data were analyzed thematically, while quantitative data were examined using descriptive statistics. Results: The findings indicate that the E-Samsat system has improved accessibility and convenience for taxpayers, yet significant challenges persist, including inadequate internet infrastructure in rural areas, low levels of digital literacy, and concerns regarding system security. Despite these barriers, the study highlights opportunities for strengthening public compliance and government revenue through infrastructure improvements, expanded socialization programs, and enhanced security measures. Novelty: This research contributes new insights into the digital transformation of taxation systems in Indonesia by addressing both the limitations and potential of E-Samsat. The study offers practical recommendations for optimizing system effectiveness and provides a framework for advancing efficient and sustainable public service innovations in local governance.